Zooming out : the trade effect of the euro in historical perspective - Helge Berger; Volker Nitsch (Center for Economic Studies and ifo Institute (CESifo), 2005)
In 1999, eleven European countries formed the Economic and Monetary Union (EMU); they abandoned their national currencies and adopted a new common currency, the euro. Several recent papers argue that the introduction of the euro has led (by itself) to a sizable and statistically significant increase in trade between the member countries of EMU. In this paper, we put the trade effect of the euro in historical perspective. We argue that the creation of the EMU was a continuation (or culmination) of a series of previous policy changes that have led over the last five decades to greater economic integration among the countries that now constitute EMU. Using a data set that includes 22 industrial countries from 1948 to 2003, we find strong evidence of a gradual increase in trade intensity between European countries. Once we control for this trend in trade integration, the euro's impact on trade disappears. Moreover, a significant part of the trend in European trade integration is explained by measurable policy changes.
Keywords: F02; F15; F33; 330; monetary union; currency; euro; trade; European integration; Europäische Wirtschafts- und Währungsunion; Aussenhandelseffekt; EU-Binnenhandel; Europäische Integration; Schätzung; EU-Staaten